Pop-up cycling infrastructure as a niche innovation for sustainable transportation in European cities: An inter- and transdisciplinary case study of Berlin. (December 2022) - Becker, Sophia; von Schneidemesser, Dirk; Caseiro, Alexandre; Götting, Katharina; Schmitz, Seán; von Schneidemesser, Erika
Highlights: Air quality measurements show that pop-up bike lanes reduce cyclists' exposure to NO2 . Survey data shows high social acceptance for pop-up bike lanes. Usage data reveals 73% increase in cycling on the pop-up bike lane. Pre-existing multi-actor collaboration enabled fast infrastructure implementation. Pop-up bike lanes can accelerate the implementation of the mobility transition. Abstract: Mobility behavior changes due to the COVID-19 pandemic have opened a window of opportunity for an accelerated transition towards sustainable mobility. Many European cities installed temporary cycling infrastructure which can be considered a niche innovation in the Multi-Level-Perspective of transitions (Geels, 2002). We empirically assess the effects of such temporary infrastructure in terms of air quality, behaviour, and acceptance, with a focus on the city of Berlin, Germany. The numerous pop-up bike lanes installed serve as an inter- and transdisciplinary case study to systematically capture these effects. We conducted a survey among Berlin citizens (n= 1, 661), analysed cycling usage data, and measured the exposure of cyclists to air quality before and after the implementation of one pop-up bike lane during the first wave of COVID-19. Results show that pop-up bike lanes receive high levels of acceptance, increase cycling usage on the respective street, and reduce cyclists' exposure to nitrogen dioxide. Their implementation fosters an innovative mind-set of transport planning: to temporarily try out new street designs, learn from these practical experiences, improve the designs, and then permanently implement the ones best proven in practice. We conclude that PUBL can accelerate the regime shift from car-oriented to bicycle-friendly cities because of its many demonstrated positive impacts.